2011
DOI: 10.1002/jssc.201100489
|View full text |Cite
|
Sign up to set email alerts
|

A new HPLC method with fluorescence detection for the determination of memantine in human plasma

Abstract: A sensitive, selective, simple and fast HPLC method based on the formation of derivative with fluorescamine was developed for the determination of memantine (ME) in human plasma. Separation was achieved on a CN column (200 mm×4.6 mm) using acetonitrile-10 mM orthophosphoric acid containing 1 mL/L triethylamine (45:55, v/v) at a flow rate of 1 mL/min. Emission and excitation wavelengths were 480 and 380 nm, respectively. Amantadine was used as an internal standard. Calibration graphs were rectilinear over the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This method is inexpensive, simple and sensitive (LOD = 1ng/ml). The derivatization employed here is a modification of the one used by S.E Toker et al (40). Gas or liquid-chromatographic-mass spectral (MS) methods for MDA measurement are an alternative to the HPLC-fluorescence method developed for antigen characterization.…”
Section: Discussionmentioning
confidence: 99%
“…This method is inexpensive, simple and sensitive (LOD = 1ng/ml). The derivatization employed here is a modification of the one used by S.E Toker et al (40). Gas or liquid-chromatographic-mass spectral (MS) methods for MDA measurement are an alternative to the HPLC-fluorescence method developed for antigen characterization.…”
Section: Discussionmentioning
confidence: 99%
“…spectrofluorometry [7][8][9], GC-MS [10,11], HPLC-MS [12][13][14] and HPLC with UV-Visible [15] and fluorescence detection [16][17][18][19][20]. In cases of UV or fluorescence detection, derivatization procedures are required to enable their detection.…”
Section: F I G U R E 1 Structures Of Adamantane Drugs and Brompheniramentioning
confidence: 99%
“…Analytical methods for assays of memantine, amantadine, and rimantadine are available in pharmacopeias (e.g. The United States Pharmacopeia (USP) and British Pharmacopoeias (BP) ) and the literature . Most methods avoid the use of optical detection (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, it has been reported that memantine was subjected to be pre-derivatized with some reagents including 9-fluorenylmethyl-chloroformate (FMOC) and dansyl chloride etc. in order to be readily detected for UV- (Narola et al 2010;Haen et al 2012;Jalalizadeh et al 2013;Michail et al 2013) or fluorescence- (Higashi et al 2006;Zarghi et al 2010;Xie et al 2011;Puente et al 2011;Toker et al 2011;Hassan et al 2012;Tekkeli and Toker 2013) high performance liquid chromatography (HPLC) in pharmaceutical dosage forms and/or biological samples such as plasma/serum of animals and human. Although previous papers well reported validated data and practical applications including pharmacokinetic studies, most of previous studies likely focus on the development and validation of bio-analytical methods mostly using fluorescence-HPLC, even required by expensive and tedious sample preparations such as liquidliquid extraction or solid-phase extraction.…”
Section: Introductionmentioning
confidence: 99%